Comparison of Neurospora crassa and Neurospora sitophila for phytase production at various fermentation temperatures - ATIT KANTI; I MADE SUDIANA (Biodiversitas Journal of Biological Diversity, 2016)
Kanti A, Sudiana IM. 2016. Comparison of Neurospora crassa and Neurospora sitophila for phytase production at various fermentation temperatures. Biodiversitas 17: 769-775. There is general consensus that the presence of phytate in poultry negatively influences protein in and energy utilization by poultry, and these influences would be mitigated by augmentation of hydrolytic enzymes. The objective of this study was to evaluate phytase production by Neurospora crassa and Neurospora sitophila on solid state fermentation. The isolates were isolated from oncom Bogor. Phytase production ability was first determined on submerge fermentation (SmF) using glucose as the main C-sources, and on solid state fermentation (SSF) on media containing maize 30%, soybean 30%, and rice brand 40% w/w. Maximum enzyme activities were observed at 96 h incubation. SSF produce higher phytase than SmF. Optimum temperature for phytase production was 35Â°C. Highest phytase production by Neurospora crassa was 45.25 Unit per g substrate, while 40.78 Unit per g substrate was produced by Neurospora sitophila. Peptone and yeast extract were good N-sources for both isolates. Starch supplement increased phytase activity. Increased amylase activity was also observed when starch supplement was added on SSF. This study proves that Neurospora crassa and Neurospora sitophila can be used to produce phytase for better poultry nutrition. Keywords: Neurospora crassa, Neurospora sitophila, phytase, solid state fermentation